INFLUENCE OF THE SMART HOME TECHNOLOGIES ON THE INTERIOR DESIGN PRINCIPALS - Kokorska, Maria (Innovation in Woodworking Industry and Engineering design, 2026)
The features of the smart interior design are considered: area minimization, modes of operation, used materials and environmental changes.A completely new services, provided by the smart interior are discovered, such as prevention of wrong actions, prediction of future actions and personalized services. Based on the above the extraction of new interior design principals (focused on the kitchen design) are concluded.